KONTRIBUSI USAHATANI TEMBAKAU TERHADAP PENDAPATAN RUMAH TANGGA DI DESA WUNGUREJO KECAMATAN RINGINARUM KABUPATEN KENDAL - Yeni Selfia; Nanik Hidayati; Abdul Majid; Mei Shinta Kussetyaning Hikmah (Sepa, 2022)
The area of tobacco plantations owned by farmers in Wungurejo Village does not guarantee the high yields produced so that it greatly affects the household income of farmers. The purpose of this study was to determine how much tobacco farming contributes to farmers' household income and what are the driving and inhibiting factors for tobacco farming in Wungurejo Village. Determination of respondents was done by purposive sampling method amounted to 38 tobacco farmers. The research phase starts from the pre-field stage, the field work stage, and the data analysis stage. This study uses a descriptive qualitative and quantitative approach. The results showed that in general the total household income of tobacco farmers was 60.53% with a total income of > 5,000,000-7,500,000 per month. Tobacco farming income gave the largest contribution, namely 58.26% of the total household income. This shows that more than half of the household income of farmers in Wungurejo Village comes from tobacco farming. Factor driving farmers in the Wungurejo to run a tobacco farm is suitable climatic conditions, the status of private land ownership, and availability of labor. While the inhibiting factors experienced by farmers such as limited business capital, lack of understanding of farmers about tobacco cultivation, and the government has never held counseling on tobacco cultivation.